Project management : an effective new tool for managing HIV/AIDS and population projects - Raimondo, P. (2001)
Provides information on a guide developed to improve the monitoring and assessment of HIV/AIDS and population projects. Notes that the guide, which is user friendly and novel in design, is an information system supplied on an interactive CD-ROM.